Tate Report : Tate Gallery Biennial Report 1996-98. - Tate Gallery, London (London : Tate Gallery, 1998)
Absalon ; Ackroyd, Norman ; Adshead, Mary ; Andre, Carl ; Angel, A.H. ; Armfield, Maxwell Ashby ; Artschwager, Richard ; Austen, David ; Ayres, Gillian ; Ayrton, Michael ; Bacon, Francis ; Balka, Miroslaw ; Banting, John ; Bartle, Anita ; Baselitz, Georg ; Bellany, John ; Beuys, Joseph ; Bevan, Tony ; Bond, Henry ; Bone, Stephen ; Brancusi, Constantin ; Brisley, Stuart ; Brown, Don ; Buckley, Stephen ; Burney, Edward Francis ; Calder, Alexander ; Callery, Simon ; Caro, Anthony ; Caulfield, Patrick ; Chadwick, Helen ; Chapman, Dinos & Jake ; Charlton, Evan ; Clemente, Francesco ; Clough, Prunella ; Coldstream, William ; Coleman, James ; Collins, Cecil ; Collins, Elisabeth ; Collishaw, Mat ; Compston, Joshua ; Cordell, Magda ; Cozens, Alexander ; Cragg, Tony (Anthony) ; Craig-Martin, Michael ; Cre, Lilian Browse ; Davey, Grenville ; Deacon, Richard ; Demand, Thomas ; Denis, Dominic ; Dickenson, Mark ; Dodgson, John ; Doig, Peter ; Doron, Itai ; Downton, John ; Dubuffet, Jean ; Duchamp, Marcel ; Durst, Alan ; Emin, Tracey ; Epstein, Sir Jacob ; Eyton, Anthony ; Fairhurst, Angus ; Fautrier, Jean ; Fedden, Mary ; Feibusch, Hans ; Fielding, Brian ; Förg, Gunther ; Freud, Lucian ; Frink, Dame Elisabeth ; Frize, Bernard ; Frost, Terry ; Fuller, Peter ; Gaudier-Brzeska, Henri ; Gilbert & George ; Gilbert, Stephen ; Gillick, Liam ; Goldin, Nan ; Gordon, Douglas ; Gormley, Antony ; Gunning, Lucy ; Guston, Philip ; Hambling, Maggi ; Hamilton, Ann ; Hamilton, Richard ; Hartung, Hans ; Hatoum, Mona ; Heindorff, Michael ; Hepworth, Barbara ; Herman, Andrew ; Hill, Gary ; Hirst, Damien ; Hockney, David ; Hodgkin, Howard ; Hodgkin, Sir Howard ; Hogarth, William ; Horn, Roni ; Hubbard, John ; Hugonin, James ; Hulbert, Thelma ; Hume, Gary ; Irvin, Albert ; IthellColquhoun ; etc.
Biografie
Contents: Achievements of the Biennium ; Tate Gallery St Ives ; Tate Gallery Liverpool ; Gifts to the Collection ; Acquisitions for the Collection 1996-98 ; loans ; exhibitions ; publications ; ...
boek